Editor's Choice: Defining "drinking culture": A critical review of its meaning and connotation in social research on alcohol problems. (3rd July 2016) - Savic, Michael; Room, Robin; Mugavin, Janette; Pennay, Amy; Livingston, Michael
Abstract: There has been growing academic interest in "drinking cultures" as targets of investigation and intervention, driven often by policy discourse about "changing the drinking culture". In this article, we conduct a critical review of the alcohol research literature to examine how the concept of drinking culture has been understood and employed, particularly in work that views alcohol through a problem lens. Much of the alcohol research discussion on drinking culture has focussed on national drinking cultures in which the cultural entity of concern is the nation or society as a whole (macro-level). In this respect, there has been a comparative tradition concerned with categorising drinking cultures into typologies (e.g. "wet" and "dry" cultures). Although overtly focused on patterns of drinking and problems at the macro-level, this tradition also points to a multifaceted understanding of drinking cultures. Even though norms about drinking are not uniform within and across countries there has been relatively less focus in the alcohol research literature on cultural entities below the level of the culture as a whole (micro-level). We conclude by offering a working definition, which underscores the multidimensional and interactive nature of the drinking culture concept.